Out-of-Pocket Expenditure and Patient Satisfaction in Developed vs. Least Developed Societies: Shifting the Balance towards Patients - Selimuzzaman, S M (Bangladesh Armed Forces Medical Journal, 2025)
Abstract not Available Bangladesh Armed Forces Med J Vol 58 No (1) June 2025, pp ii-iv